A partitioned solver for compressible/incompressible fluid flow and light structure. (15th October 2021) - Garg, Deepak; Papale, Paolo; Longo, Antonella
Abstract: In this work, a partitioned fluid-structure interaction solver is presented. Fluid flow problem is solved with time-discontinuous deforming domain stabilized space-time finite element method. Flow is computed with pressure primitive variables which permit to use the same numerical technique for both compressible and incompressible regimes. Elastic deformation of the structure is modelled in the Lagrangian frame of reference with Saint-Venant Kirchhoff and Neo-Hookean material models - both are non-linear and valid for large deformations. Structure equations are discretized with Galerkin finite element method for space and with generalized-alpha method for the time. Mesh motion is modelled with the elastic deformation method. An implicit algorithm is presented to couple the different solvers. The details are provided on the implementation of the solvers in parallel software. The numerical code is verified and validated on several compressible and incompressible flow benchmarks widely used in the literature. The results demonstrate that the developed solver successfully detects the accurate interaction between fluid and structure.